Common Difficulties of Eighth Grade Students When Solving Non-Routine Mathematics Problems - Ratnasari, Ratnasari; TLS, Desyarti Safarini (FKIP Universitas Lampung, 2022)
The study's objective is to investigate common difficulties experienced by 8th-grade students when solving non-routine mathematics problems. This study used a qualitative descriptive method, and the research participants were eighth-graders students at one of the private middle schools in Jakarta. The researchers used a convenience sample to obtain a group of six students available for an in-depth interview session and willing to solve two non-routine problems related to algebra topic. The study showed that the participants experienced difficulties when solving non-routine mathematics problems. They could not read the problem comprehensively; they had trouble converting the word problems into mathematical sentences. They also had difficulty in carrying out their plans. In other words, students did not have the strategy to solve the problem. They had errors in the calculation and had incorrect formulations when solving the given problems. It is suggested that the teacher provide students with guiding instructions to assist students in going through the problem-solving phases step by step. The teacher can also highlight the non-routine problem's keywords and give a representation that helps students understand the problem. Keywords: learning difficulties, middle school students, mathematics problems DOI: http://dx.doi.org/10.23960/jpmipa/v23i1.pp67-77